Perbedaan Pendapatan Peralihan Lahan Usahatani Padi Sawah menjadi Usahatani Jeruk Nipis di Desa Watabenua Kecamatan Landono Kabupaten Konawe Selatan - Fausayana, Ine; Miniarti, Yustina; Rosmawaty, Rosmawaty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This study aims to determine the differences in income before and after farmers make shifts of rice paddy farming land into lime farming in Watabenua Village, Landono District, South Konawe Regency. The number of samples used in this study was 33 people. The sample used was rice paddy farmers who transitioned their rice fields into lime plants. The data analysis method used in the study was a different test paired sample t-test. The results showed that the results of the analysis of different test paired sample t-test with Î± = 5% showed that there were significant differences from the average income of farmers before and after transitioning rice fields into lime farming, namely changes in income from Rp. 705 / year to Rp.26,520,258 / year so that the transition of paddy fields has a significant influence on farmer's income in Watabenua Village, Landono Subdistrict, South Konawe Regency.